Analysis of Factors that Affect Marketing Performance in PT. Bayu Buana Gemilang Reviewed From Sharia Perspective - Lusi Dewi; Mukhamad Najib; Mukhamad Yasid (ILTIZAM Journal of Shariah Economics Research, 2021)
This study aims to analyze the factors that influence marketing performance at PT. Bayu Buana Gemilang from a Sharia perspective. Using the Structural Equation Model (SEM) approach of 126 employees, 40 samples are taken to be sampled. This research has been attempted in accordance with scientific procedures, Testing is carried out on three variables namely work, program marketing, and corporate culture. Corporate culture is a tool for companies in carrying out strategic policies that play a role in encouraging improving quality, motivation and employee work performance. Based on the results of the study conclusions can be drawn Work orientation, marketing programs and corporate culture affect marketing performance and show positive results.